Exploring the Utilization of ICT in Physics Learning at Senior High Schools in Demak: Opportunities and Challenges - Sulistyani, Dyah Catur; Mochama, Omosa Elijah (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to explore the use of ICT-based physics learning media by physics teachers in high schools in Demak Regency. In addition, this study identifies challenges and opportunities in the application of ICT to improve the quality of physics learning. Methodology: This study uses a qualitative approach with a case study method. Data were collected through structured interviews using a questionnaire, as well as documentation related to ICT infrastructure. Purposive sampling technique was used to select two physics teachers and six students at State Senior High School 3 Demak. Data analysis refers to the Miles and Huberman model, which includes data reduction, data presentation, and drawing conclusions. Main Findings: This study found that the use of ICT-based learning media in physics learning at State Senior High School 3 Demak can improve students' understanding of abstract concepts. Teachers used PowerPoint, learning videos, simulations, and digital platforms. The main challenges included limited ICT facilities, unstable internet connections, and teachers' diverse technological skills. Students showed positive responses to ICT-based learning, but still needed a combination of conventional methods. Adaptive strategies are needed to overcome the constraints of technology accessibility. Novelty/Originality of this study: This study enriches the literature with an in-depth case study approach, reveals practical solutions in ICT integration, and emphasizes the importance of a combination of conventional and digital methods for learning effectiveness.